Determination of Aminophylline by Cathodic Stripping Voltammetry - Raqi Shubietah (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
Aminophylline is determined by cathodic stripping voltammetry (CSV) in BR buffer, pH 7.5 at a hanging mercury drop electrode. The detection limit was 3x10-8 M after 60 s accumulation at -0.60 V versus Ag/AgCl reference electrode. The linear range demonstrated up to 5x10-7 M using CSV. The interference caused by some purine derivatives, anions and some metal cations on the peak current was studied. The peak current is enhanced by theophylline, some methylguanines and copper (II) while it decreased or disappeared by citrate, chloride and Triton X-100 surfactant. The method has good sensitivity and its application to pharmaceutical samples is possible. Keywords: Determination of aminophylline, stripping voltammetry, cathodic stripping voltammetry, adsorptive voltammetry, dosage forms